HrcA-mediated transcriptional regulation affects the growth and survival of Streptococcus suis under low-glucose conditions - Ran Liu; Shulin Miao; Kunlong Xia; Yuhua Wang; Long Li; Anding Zhang (Animal Diseases)
Abstract Streptococcus suis (S. suis) is a major zoonotic pathogen whose nasopharyngeal colonization relies on adaptive regulation in response to the host’s low-glucose microenvironment. However, the molecular mechanisms underlying this adaptation remain largely unexplored. In this study, RNA-seq analysis of S. suis cultured under low-glucose (0.2%) conditions revealed 86 DEGs, predominantly associated with the phosphotransferase system, alternative carbon metabolism, and energy homeostasis pathways. A phenotypic screening of eight transcription factor (TF) mutants revealed that deletion of HrcA significantly impaired bacterial growth and survival under low-glucose conditions. ChIP-seq analysis revealed the HrcA-binding motif (GTGCTAATT) and mapped 391 potential target genes, 18 of which were differentially expressed under low-glucose conditions. Further qPCR and electrophoretic mobility shift assays (EMSAs) validated the direct regulation of 10 target genes by HrcA. Specifically, HrcA represses energy-intensive genes (B9H01_00980 and B9H01_04980) to conserve energy while activating B9H01_00995 and B9H01_01125 to promote alternative carbon metabolism and pyruvate fermentation. Additionally, HrcA modulates the expression of the AraC family TF1 and the DeoR family TF4, establishing a hierarchical regulatory network. Notably, HrcA downregulates its own expression under low-glucose conditions to fine-tune carbon metabolism gene regulation and maintain S. suis homeostasis, providing new insights into its adaptive strategies.